2001
DOI: 10.1093/humrep/16.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Decreased fertilization rate and embryo quality after ICSI in oligozoospermic men with microdeletions in the azoospermia factor c region of the Y chromosome

Abstract: Microdeletions of the azoospermia factor (AZF) region of the Y chromosome occur in between 1 and 29% of oligozoospermic and azoospermic men, and most deletions are found in the AZFc region. These men can father children when intracytoplasmic sperm injection (ICSI) is used, but the success rate is unclear. Thus, the success rate of 19 ICSI treatments in eight couples with a microdeletion in the AZFc region of the Y chromosome was analysed retrospectively. These were compared with a control group of 239 ICSI tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
1
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 26 publications
6
72
1
4
Order By: Relevance
“…Our study shows that Y chromosome AZFc microdeletion group has a reduced fertilization rate and an increased cleaved embryo rate compared with men without microdeletion and the difference is statistically significant. The reduced fertilization rate is consistent with the result reported by van Golde RJ et al [9]. This result suggests that Y chromosome AZFc microdeletion would affect the fertilization rate of ICSI treatment, leading to reduced fertilizing ability of sperm, and therefore an inability to activate oocytes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study shows that Y chromosome AZFc microdeletion group has a reduced fertilization rate and an increased cleaved embryo rate compared with men without microdeletion and the difference is statistically significant. The reduced fertilization rate is consistent with the result reported by van Golde RJ et al [9]. This result suggests that Y chromosome AZFc microdeletion would affect the fertilization rate of ICSI treatment, leading to reduced fertilizing ability of sperm, and therefore an inability to activate oocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirmed the results of previous studies [24,25] in a larger cohort. Recently, several investigators have shown that embryo characteristics following ICSI using sperm obtained from men with Y chromosome microdeletions were not adversely affected by the deletion [4,9,10,26,27]. ICSI brings new hope for severe oligozoospermic men who wish to conceive children with their own gametes [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, men with Yq microdeletions have poor embryo quality and lower success rates of ICSI as compared to non-deleted counterparts [5,39]. However, the contribution of AZFc subdeletions on outcome of assisted reproduction is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Since men with deletions of entire AZFc have poor outcome after assisted reproduction [5,39], we also investigated if the AZFc subdeletions have any influence on fertilization rate, embryo transfer rate, embryo quality and pregnancy outcome in male partners of couples undergoing ICSI (intracytoplasmic sperm injection).…”
Section: Introductionmentioning
confidence: 99%